The Importance of Bacteriological Studies of Upper Respiratory Tract Diseases in Children and the Relevance of their Improvement - qizi, Madinakhon Moʻminova Abdulkhaq; qizi, Maftuna Khurramova Sherali; Shavkatovich, Dilmurod Khalniyazov (American Journal of Biology and Natural Sciences, 2025)
Worldwide, respiratory infections in children, including those caused by bacteria and viruses, are one of the main causes of morbidity and mortality. Immune activation, inflammation, and metabolic changes are some of the unique pathophysiological processes that define these infections. Gaining knowledge of the molecular processes that underlie these infections helps with diagnosis, treatment planning, and the function of nursing treatments. For pediatric respiratory infections to improve outcomes and reduce complications, effective care is essential. This review’s objective is to present a current examination of the pathophysiology, biochemical elements, diagnostic methods, available treatments, and nursing interventions for pediatric respiratory infections. It draws attention to important elements such age-related variations, the function of immunological responses, and evidence-based nursing care techniques. This review provides a thorough overview of pediatric respiratory infections by synthesizing the body of research from clinical studies, case reports, and biochemical analysis. The origin of infections, immune response mechanisms, clinical symptoms, biochemical indicators for diagnosis and monitoring, and nurse management treatments are some of the important topics discussed. Children’s respiratory infections are frequently caused by bacterial pathogens like Streptococcus pneumonia and viral agents like influenza and respiratory syncytial virus (RSV). Immune responses triggered by these infections include the release of biochemical markers including procalcitonin (PCT) and C-reactive protein (CRP) as well as inflammatory cytokines. Comprehensive nursing treatments, including as respiratory support, temperature regulation, and hydration, are necessary for the clinical management of these illnesses. Family support and psychological care are also important components of healing. Children’s respiratory infections are complicated, combining clinical, immunological, and biochemical elements. Diagnosis and successful therapy are facilitated by knowledge of the pathophysiology and biochemical indicators. In order to control symptoms, ensure patient comfort and stop the spread of infection, nursing interventions are crucial. Children that are impacted can benefit from early intervention and holistic care methods.